Pendampingan Penggunaan Aplikasi Mendeley Reference bagi Guru Sekolah Dasar Negeri Binaan Khusus Dumai Timur - Andriyani, Noni; Erni, Erni; Fitriah, Laila (Fakultas Teknik Universitas Lancang Kuning, 2025)
The teachers of SDN Binaan Khusus Dumai Timur still have minimal knowledge of scientific publications and the scientific publication citation system. In fact, most teachers have never known applications that can help write citations and bibliographies automatically. In fact, the ability to write citations, especially with the Mendeley Reference application, is often one of the provisions of current scientific publications and scientific publications are a requirement for submitting promotions to elementary school teachers in group IV/b. Meanwhile, the requirement for submitting a promotion under IV/b is that elementary school teachers must have scientific work. Thus, elementary school teachers in general, teachers at SDN Binaan Khusus Dumai Timur in particular, must have the ability to write citations and bibliographies properly and correctly. Therefore, it is necessary to carry out guidance and training related to writing good and correct citations and bibliographies for teachers of the SDN Binaan Khusus Dumai Timur. The Mendeley Reference application is considered the most commonly used for citation rules and bibliographies of scientific publications at this time, so this application was chosen to be taught to the teachers ofSDN Binaan Khusus Dumai Timur. PkM is carried out using the PAR (Participatory Action Research) method. The results of this PkM show that the small production of scientific writing and scientific publications by the partner groups is due to various reasons, and one of them is due to the unfamiliarity of the partner groups to new technologies in scientific writing and scientific publications. After receiving a tutorial on using the Mendeley Reference application, the partner group agreed that this application would greatly facilitate the writing of citation systems and bibliographies in scientific writing and scientific publications.